Analisa Total Harmonic Distortion dan Losses Setelah Beroperasinya Distributed Generation di Program Studi Teknik Elektro Universitas Udayana - Dwi Nugroho, Gregorius Reza; Rinas, I Wayan; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 6 No 1 (2019): Jurnal SPEKTRUM, 2019)
In the Electrical Engineering Study Program, Udayana University, a Solar Power Plant was installed with a power of 26.4 kWp, a Wind Power Plant with a power of 5 kWp and a Diesel Power Plant with a capacity of 20 kVA. The size of harmonics in the electric power system is called Total Harmonic Distortion (THD). THDi's research results at DH Electrical Engineering Building of Udayana University before the operation of Distributed Generation (DG) were that R phase was 9.91%, S phase was 10.86%, and T phase was 9.85%. THDi value after the operation of Distributed Generation, R phase was 16.05%, S phase was 17.53%, and T phase was 15.70%. THDi value with LC filter, R phase was 4.0%, S phase was 5.52% and T phase was 3.97%. THDv value before the operation of Distributed Generation, R phase was 0.08%, S phase was 0.48% and T phase was 0.47%. THDv value after the operation of Distributed Generation, R phase was 0.24%, S phase was 0.44% and T phase was 0.49%. THDv value with LC filter, R phase was 0.01%, S phase was 0.01% and T phase was 0.02%. The results of the research showed that losses before the operation of Distributed Generation were 115.53 Watts and the value of losses after the operation of Distributed Generation had increased to 130.07 Watts.